1981
DOI: 10.1099/00221287-122-2-171
|View full text |Cite
|
Sign up to set email alerts
|

Partial Replacement of Succinate Dehydrogenase Function by Phage- and Plasmid-specified Fumarate Reductase in Escherichia coli

Abstract: Phages capable of transducing succinate dehydrogenase mutants (sdh) of Escherichia coli were isolated from pools of artificially constructed recombinant lambda phages using a selective casein digest medium. These phages produced characteristically dense turbid plaques, and as prophages they increased the aerobic growth efficiencies of sdh mutants on complex media but were unable to promote growth with succinate as sole carbon and energy source (an essential feature of sdh + strains). The phages were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 11 publications
4
54
0
Order By: Relevance
“…Under these conditions, a functional FRD is required; i.e., E. coli DW35 does not grow in either of these media. FRD when expressed from multicopy plasmids is fully capable of functionally replacing SDH in E. coli (13). FRD when expressed has, in fact, the same turnover number for succinate oxidation as native E. coli SDH (2, 33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under these conditions, a functional FRD is required; i.e., E. coli DW35 does not grow in either of these media. FRD when expressed from multicopy plasmids is fully capable of functionally replacing SDH in E. coli (13). FRD when expressed has, in fact, the same turnover number for succinate oxidation as native E. coli SDH (2, 33).…”
Section: Resultsmentioning
confidence: 99%
“…E. coli FRD catalyzes succinate oxidation at rates similar to that of the native SDH of that organism (2) and at about 30 to 40% of the rate at which it reduces fumarate (8). The frd gene products will replace SDH in sdh mutants when expressed from multicopy plasmids (13). It has been proposed, on the basis of sequence comparison of the catalytic domain subunits of FRD and SDH, that the genes are of common ancestral origin (41).…”
mentioning
confidence: 99%
“…However, their experiments did show activity for fumarate reductase. Evidence was presented previously which showed that fumarate reductase can compensate for a loss of succinate dehydrogenase (35,36). This could putatively convert succinate to fumarate.…”
Section: Figmentioning
confidence: 99%
“…The complex media were L broth for routine subculture and peptone broth for specific growth tests (Guest, 1981), supplemented as required with ampicillin (100 pg ml-'), chloramphenicol (25 pg ml-'), kanamycin (15 pg ml-') and glucose (50 mM). The citrate-free minimal medium (Cole & Guest, 1980) was used with glucose (20 mM), sodium acetate (40 mM), sodium succinate (40 mM), sodium DL-lactate (40 mM) or sodium pyruvate (40 mM) as carbon sources, and supplements of thiamin hydrochloride (5 pg ml-l) and L-glutamate (2 mM) or L-proline (0.22 mM), as required.…”
Section: --mentioning
confidence: 99%